REVIEW ON THE GENETIC DIVERSITY IN LINSEED (LINUMUSITATISSIMUM L.) IN THE HIGHLANDS OF ETHIOPIA. - Berhanu Sime Tulu (International Journal of Multidisciplinary Research and Studies, 2022)
Linseed is a multipurpose crop grown for the production of stem fiber and seed oil. Linseed Domestication has been inferred genetically from neutral markers and increasingly from specific domestication–associated locus. However, some crops are utilized for multiple purposes that may or may not be reflected in a single domestication-associated locus. Due to long-term domestication for the fulfillment of these purposes, cultivated flax has diversified into two main types, namely fiber and oil or linseed types, as well as an intermediate type. These types differ considerably in morphology, growth habits, and agronomic traits. Fiber-type plants are usually taller and have fewer branches while linseed types are often shorter, have more branches, and produce more seeds. The center of origin of flax or Linseed (Linumusitatissimum L.) is uncertain. It is considered that L. Bienne is the progenitor of small-seeded flax, originating from Kurdistan and Iran, Flax or Linseed is indigenous to the region expanding from the eastern Mediterranean to India, and was presumably first domesticated in the Fertile Crescent. Flax is an annual plant growing 120 cm tall, with slender stems. The leaves are green, 20-40 mm long and 3 mm broad. The flowers are majorly pure pale blue and of various other colors, 15-25 mm in diameter, with five petals.